PEMBERIAN ETANOL JANGKA PANJANG MENURUNKAN MEMORI KERJA SPASIAL PADA TIKUS - Aswin, Soedjono; Mustofa, Mustofa (Jurnal Kedokteran Brawijaya, 2008)
Long term ethanol administration may cause morphological changes in the hippocampus, followed by deficit in  the  hippocampal  function  including  the  impairment  of  memory.  The  aim  of  this  study  is  to  investigate  the changes of spatial working memory of rats after chronic ethanol administration at adolescent age. Twenty five adolescent  (30  days  of  age)  male  rats  (Rattus  novergicus)  divided  randomly  into  5  groups  :  control  without treatment (C1), control with treatment (C2), treatment 1 (T1), treatment 2 (T2), treatment 3 (T3) group. Each group consist of 5 rats. C2 group was given physiologic saline, T1, T2, and T3 group were given ethanol with doses  1,  2,  and  3  g/kg/day  for  30  days  by  intraperitoneal  injection.  After  chronic  ethanol  administration  the spatial  working  memory  of  5  groups  were  tested  by  using  8  arm  radial  maze  for  12  days.  Spatial  working memory measured by total number of entered arm maze and error A type. The results of this study showed that  chronic  ethanol  administration  at  adolescent  age  caused  decreasing  of  spatial  working  memory  of  the rats. The total number of entered arms maze and error A type for treatment group (especially P3 ) is higher than  control  groups  (p<0,05).  It  is  concluded  that  in  rats,  chronic  ethanol  administration  at  adolescent  age caused decreasing spatial working memory.   Key words : Ethanol, Spatial working memory, Adolescent